Respuestas
Respuesta dada por:
1
Bueno :
1) 2/3 (2y/5 +3/6) =2/3 (2y/4-3/5)
=> 2y/5 + 3/6 =2y/4 - 3/5
=> 4y + 5 = 5y -6
=> y=11
2) x/3 -2 = x/9
=> (x-6)/3 = x/9
=> x-6 = x/3
=> 3(x-6) =x
=> 3x-18=x
=> 2x=18
=> x=9
Espero te sirva!!!
1) 2/3 (2y/5 +3/6) =2/3 (2y/4-3/5)
=> 2y/5 + 3/6 =2y/4 - 3/5
=> 4y + 5 = 5y -6
=> y=11
2) x/3 -2 = x/9
=> (x-6)/3 = x/9
=> x-6 = x/3
=> 3(x-6) =x
=> 3x-18=x
=> 2x=18
=> x=9
Espero te sirva!!!
Respuesta dada por:
1
¡Hola!
I.
![\frac{2}{3} ( \frac{2}{5} y + \frac{3}{6} ) = \frac{2}{3} ( \frac{2}{4} y - \frac{3}{5} ) \\ \frac{2}{5} y + \frac{3}{6} = \frac{2}{3} \div \frac{2}{3} ( \frac{2}{4} y - \frac{3}{5} ) \\ \frac{2}{5} y + \frac{1}{2} = \frac{1}{2} y - \frac{3}{5} \\ \frac{1}{2} + \frac{3}{5} = \frac{1}{2} y - \frac{2}{5} y \\ \frac{11}{10} = \frac{1}{10} y \\ \frac{11 \times 10}{10} = y \\ 11 = y \frac{2}{3} ( \frac{2}{5} y + \frac{3}{6} ) = \frac{2}{3} ( \frac{2}{4} y - \frac{3}{5} ) \\ \frac{2}{5} y + \frac{3}{6} = \frac{2}{3} \div \frac{2}{3} ( \frac{2}{4} y - \frac{3}{5} ) \\ \frac{2}{5} y + \frac{1}{2} = \frac{1}{2} y - \frac{3}{5} \\ \frac{1}{2} + \frac{3}{5} = \frac{1}{2} y - \frac{2}{5} y \\ \frac{11}{10} = \frac{1}{10} y \\ \frac{11 \times 10}{10} = y \\ 11 = y](https://tex.z-dn.net/?f=+%5Cfrac%7B2%7D%7B3%7D+%28+%5Cfrac%7B2%7D%7B5%7D+y+%2B++%5Cfrac%7B3%7D%7B6%7D+%29+%3D++%5Cfrac%7B2%7D%7B3%7D+%28+%5Cfrac%7B2%7D%7B4%7D+y+-++%5Cfrac%7B3%7D%7B5%7D+%29+%5C%5C++%5Cfrac%7B2%7D%7B5%7D+y+%2B++%5Cfrac%7B3%7D%7B6%7D+++%3D++%5Cfrac%7B2%7D%7B3%7D++%5Cdiv++%5Cfrac%7B2%7D%7B3%7D+%28+%5Cfrac%7B2%7D%7B4%7D+y+-++%5Cfrac%7B3%7D%7B5%7D+%29+%5C%5C++%5Cfrac%7B2%7D%7B5%7D+y+%2B+++%5Cfrac%7B1%7D%7B2%7D++%3D++%5Cfrac%7B1%7D%7B2%7D+y++-++%5Cfrac%7B3%7D%7B5%7D++%5C%5C++%5Cfrac%7B1%7D%7B2%7D++%2B++%5Cfrac%7B3%7D%7B5%7D++%3D++%5Cfrac%7B1%7D%7B2%7D+y+-++%5Cfrac%7B2%7D%7B5%7D+y+%5C%5C++%5Cfrac%7B11%7D%7B10%7D++%3D++%5Cfrac%7B1%7D%7B10%7D+y+%5C%5C++%5Cfrac%7B11+%5Ctimes+10%7D%7B10%7D++%3D+y+%5C%5C+11+%3D+y)
II.
![\frac{x}{3} - 2 = \frac{x}{9} \\ \frac{x}{3} - \frac{x}{9} = 2 \\ \frac{6}{27} x = 2 \\ \frac{2}{9} x = 2 \\ x = 9 \frac{x}{3} - 2 = \frac{x}{9} \\ \frac{x}{3} - \frac{x}{9} = 2 \\ \frac{6}{27} x = 2 \\ \frac{2}{9} x = 2 \\ x = 9](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%7D%7B3%7D++-+2+%3D++%5Cfrac%7Bx%7D%7B9%7D++%5C%5C+++%5Cfrac%7Bx%7D%7B3%7D++-++%5Cfrac%7Bx%7D%7B9%7D++%3D+2+%5C%5C++%5Cfrac%7B6%7D%7B27%7D+x+%3D+2+%5C%5C++%5Cfrac%7B2%7D%7B9%7D++x+%3D+2+%5C%5C+x+%3D+9)
Espero que te sirva de ayuda ^^
Saludos: Margareth ✨
I.
II.
Espero que te sirva de ayuda ^^
Saludos: Margareth ✨
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años